Levels of effectiveness of the organization of educational activities of future social educators (Pedagogy of Higher and Secondary Education, 2012)
Dobroskok I. I. Levels of effectiveness of the organization of educational activities of future social educators.In the article the educational levels of the organization's effectiveness eyatelnosti future social workers. Characterized by a group of educational elements, the levels of formation of knowledge in accordance with the characteristics of future professionals.
Keywords: levels of efficiency; organization of training activities and social workers